Effects of soil cover and weed management in a coffee plantation in Nicaragua - Aguilar Bustamante, V.M. (Managua (Nicaragua), 1993)
Sumarios (Es, En)
Ilus.; 7 ref.
Tesis (Mag Sc)
Keywords: COFFEA ARABICA; MALEZAS; ESCARDA; MANEJO DEL SUELO; PLANTACION; NICARAGUA